Study on Enhancement of Microwave Absorption Properties on Modified Kapton Film by Ion Implantation Process - Purwanto, S.; Wisnu, A. A.; Taryana, Yana; Sukirman, E. (Research Trends and Challenges in Physical Science Vol. 3, 2021)
This research aims to modify Kapton-polyimide film by using ions such as iron (Fe) or Gadolinium (Gd) and to investigate the relation between the existence of the phases, magnetic properties, and microwave absorption. Kapton-polyimide films have been modified by using ion implantation of Fe and Gd ions at dose 1 × 1017 ions/cm2 and energy ions 30 keV. From X-ray diffraction (XRD) were verified the existence phases such as iron oxide, or Gd-oxide, and graphitic Carbon. Vibrating Sample Magnetometer (VSM) measurement of the films showed a paramagnetic behavior. Microwave absorption (MWA) properties were measured by Vector Network Analyzer (VNA) at the X band range (8-12GHz). VNA measurement results showed the enhancement of MWA from -22dB for Kapton original film to -35dB for at S11 vector direction and until -40 dB for S22 vector direction of modified Kapton film by Fe and Gd ions. It can be concluded that the nanostructure of embedded Fe-oxide or Gd-oxide nanoparticles on the near-surface of Kapton film takes a role and give rise to the MWA properties of the film.